An in situ and in vitro investigation of cytoplasmic TDP-43 inclusions reveals the absence of a clear amyloid signature. (31st December 2023) - Cascella, Roberta; Banchelli, Martina; Abolghasem Ghadami, Seyyed; Ami, Diletta; Gagliani, Maria Cristina; Bigi, Alessandra; Staderini, Tommaso; Tampellini, Davide; Cortese, Katia; Cecchi, Cristina; Natalello, Antonino; Adibi, Hadi; et al.
Abstract: Introduction: Several neurodegenerative conditions are associated with a common histopathology within neurons of the central nervous system, consisting of the deposition of cytoplasmic inclusions of TAR DNA-binding protein 43 (TDP-43). Such inclusions have variably been described as morphologically and molecularly ordered aggregates having amyloid properties, as filaments without the cross-β-structure and dye binding specific for amyloid, or as amorphous aggregates with no defined structure and fibrillar morphology. Aims and Methods: Here we have expressed human full-length TDP-43 in neuroblastoma x spinal cord 34 (NSC-34) cells to investigate the morphological, structural, and tinctorial properties of TDP-43 inclusions in situ . We have used last-generation amyloid diagnostic probes able to cross the cell membrane and detect amyloid in the cytoplasm and have adopted Raman and Fourier transform infrared microspectroscopies to study in situ the secondary structure of the TDP-43 protein in the inclusions. We have then used transmission electron microscopy to study the morphology of the TDP-43 inclusions. Results: The results show the absence of amyloid dye binding, the lack of an enrichment of cross-β structure in the inclusions, and of a fibrillar texture in the round inclusions. The aggregates formed in vitro from the purified protein under conditions in which it is initially native also lack all these characteristics, ruling out a clear amyloid-like signature. Conclusions: These findings indicate a low propensity of TDP-43 to form amyloid fibrils and even non-amyloid filaments, under conditions in which the protein is initially native and undergoes its typical nucleus-to-cell mislocalization. It cannot be excluded that filaments emerge on the long time scale from such inclusions, but the high propensity of the protein to form initially other types of inclusions appear to be an essential characteristic of TDP-43 proteinopathies. KEY MESSAGES: Cytoplasmic inclusions of TDP-43 formed in NSC-34 cells do not stain with amyloid-diagnostic dyes, are not enriched with cross-β structure, and do not show a fibrillar morphology. TDP-43 assemblies formed in vitro from pure TDP-43 do not have any hallmarks of amyloid.